Determinação de fatores angiogênicos e anti-angiogênicos em plasma de gestantes portadoras de pré-eclâmpsia precoce e tardia - Weel, Ingrid Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Changes in circulating angiogenic factors have been implicated in the pathogenesis of preeclampsia. Thus, evaluation of angiogenesis agonist and antagonist factors is of greater importance to understand the mechanisms responsible for this disorder. The objective of the present study was to evaluate whether circulating angiogenic and anti-angiogenic factors may differentiate early-onset from late-onset preeclampsia. The study was conducted in 86 women with preeclampsia diagnosed in the third trimester of pregnancy. Preeclampsia was classified according to the onset of clinical manifestation in early-onset (before 34 weeks of gestation; n=31) or in late-onset (from 34 weeks of gestation on; n=55) preeclampsia. Serum was obtained from the patients in the moment of the diagnosis and assayed for placental growth factor (PlGF), vascular endothelial growth factor (VEGF), soluble Endoglin (sEng) and soluble form of vascular endothelial growth factor receptor (sVEGFR-1) determination by enzyme-linked immunosorbent assay. The results showed that early-onset preeclampsia was characterized by significant lower levels of PlGF (median 38.3 vs 123.5 pg/mL) and VEGF (median 23.1 vs 35.3 pg/mL) in serum as well as by higher serum levels of sEng (median 54.7 vs 42.1 pg/mL) and sVEGFR-1 (median 5211.0 vs 4657.6 pg/mL) compared with late-onset preeclampsia. In this study serum levels of angiogenic and anti-angiogenic factors prove useful in differentiating early-onset from late-onset preeclampsia in the third trimester of pregnancy. Therefore, these findings suggest that angiogenic factors determination may indicate that early- and late-onset preeclampsia have different pathophysiology

A pré-eclâmpsia (PE) é uma síndrome específica da gestação humana, caracterizada pelo aparecimento de hipertensão arterial e proteinúria após a 20ª semana de gestação. O desbalanço entre fatores pró-angiogênicos (Fator de Crescimento Placentário-PlGF e Fator de Crescimento Endotelial Vascular-VEGF) e anti-angiogênicos (Endoglina-Eng e Receptor para VEGF- VEGF-R1) na circulação, têm sido implicado na patogênese da doença. O objetivo do presente trabalho foi avaliar se esses fatores pró e anti-angiogênicos presentes no plasma das gestantes com PE podem diferenciar PE precoce e tardia. Foram estudadas 86 gestantes, sendo 31 portadoras de PE precoce (antes de 34 semanas de gestação) e 55 portadoras de PE tardia (a partir de 34 semanas de gestação). Para quantificar os fatores pró e anti-angiogênicos, o plasma obtido a partir de sangue venoso, foi aliquotado e armazenado à - 80ºc. As amostras foram avaliadas por ensaio imunoenzimático (ELISA). Os resultados mostraram que a PE precoce foi caracterizada por níveis significantemente mais baixos de PlGF (mediana 38,3 vs 123,5 pg/mL) e VEGF (mediana 23,1 vs 35,3 pg/mL), bem como o aumento sérico de sEng (mediana 54,7 vs 42,1 pg/mL) e VEGF-R1 (mediana 5211,0 vs 4657,6 pg/mL) em relação às gestantes portadoras de PE tardia. Esses resultados sustentam a hipótese de que a circulção de fatores angiogênicos podem ser úteis na diferenciação de PE precoce ou tardia no terceiro trimestre da gravidez, indicando que o desenvolvimento precoce ou tardio da doença podem ter fisiopatologias diferentes
Keywords: Gravidez – Complicações; Pre-eclampsia; Neovascularização; Plasma sanguineo